Frequency Of Normal Variation Of Buccal And Labial Mucosa In Oral Disease Clinic Rsgm Andalas University - Haria Ftri; Gita Dwi JS; Reno Wiska Wulandari; Nila Kasuma (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Diseases or lesions of the oral mucosa are a significant aspect of oral diseases that greatly affect the patients experiencing them. Among all oral mucosal diseases, there are several conditions categorized as normal variations in the anatomical structure of the oral mucosa. Normal variations in the oral cavity are clinical presentations that are unusual. Non-pathogenic conditions, namely clinical variations in the form of uncommon organ structures with specific characteristics, fall into the category of normal and are not pathological conditions. Material and Method: This study employed observational descriptive research to examine the presentation of normal variations in the oral mucosa of patients at the oral disease clinic of the Faculty of Dentistry, Andalas University. Univariate analysis was conducted in this research to observe the distribution of normal variations in the oral mucosa. Results and Discussion: The number of samples in this study was 620 patient data, with the prevalence of normal variations in the oral mucosa found to include cheek biting, fordyce granule, linea alba, leukoderma, and irritation fibroma. The highest prevalence was cheek biting at 52.6%, while the lowest was irritation fibroma at 1.8%. Conclusion: Cheek biting is the most common normal variation in the oral mucosa observed at the oral disease clinic of the Faculty of Dentistry, Andalas University.